2010 IEEE 5th International Conference on Nano/Micro Engineered and Molecular Systems 2010
DOI: 10.1109/nems.2010.5592123
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of seamless patterns onto metal rollers by photolithography

Abstract: This paper develops a novel method to fabricate seamless and complicated patterns of microstructures onto the cylindrical surface of a metal roller. This patterned metal roller can then serve as a roller mold in roll-to-roll (R2R) continuous roller imprinting of microstructures at low-cost, high-speed, and large-area. The first step towards fabricating a seamless roller mold is a pneumatically driven and self-spinning coating method and system which can uniformly spin-coat a smooth thin photoresist (PR) layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Only a few studies have shown that it is basically possible to work with planar masks in a proximity exposure setup to lithographically structure small (and large) cylinders [22,23]. The smallest lateral structure width achieved on small cylinders was 5 µm [22].…”
Section: Rotational Uv-lithography Using Flexible Chromium-coated Pol...mentioning
confidence: 99%
“…Only a few studies have shown that it is basically possible to work with planar masks in a proximity exposure setup to lithographically structure small (and large) cylinders [22,23]. The smallest lateral structure width achieved on small cylinders was 5 µm [22].…”
Section: Rotational Uv-lithography Using Flexible Chromium-coated Pol...mentioning
confidence: 99%